ETIOPATHOGENESIS OF FACIAL PARALYSIS. IATROGENESIS IN THE DENTAL OFFICE - Aranka Ilea; Dan Buhățel; Minodora Moga; Anca Ionel; Claudia Feurdean; Radu Septimiu Câmpian (Romanian Journal of Oral Rehabilitation, 2014)
The etiopathogenesis of facial paralysis is extremely varied, from local causes to general disorders, including the side effects of some drug treatments. Iatrogenic facial paralysis induced in the dental office or during oromaxillo-facial surgery should not be neglected. Iatrogenic facial palsy in the dental office is illustrated by a case report. In order to avoid these situations, the dentist should have a good competence for the adequate management of patients with facial paralysis in the dental office.